(untitled) (Swiss Medical Weekly, 2010)
The recent European Society of Cardiology (ESC) guidelines delineate the diagnosis and management of distinct categories of acute heart failure syndromes. However, physicians dealing with these patients may need guidance in choosing therapeutic alternatives as soon as the dyspneic patient arrives at the emergency department, until distinct categories of the ESC guidelines are identified. Hence, this manuscript summarizes practical recommendations for the very early management of patients with acute heart failure syndromes. The recommendations are based on a clinical classification system considering the initial systolic blood pressure and other symptoms. Early initiation of diagnostic and goal-directed treatment strategies are key factors in improving patient outcomes. Early and frequent reassessment is also imperative so that adjustments to the initial therapeutic approach can be made, as clinically indicated.